PEMBERDAYAAN GURU DALAM IMPLEMENTASI PEMBELAJARAN ABAD 21 - Kartimi Kartimi; Asep Mulyani; Onwardono Rit Riyanto (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2019)
This form of devotion training aims to provide detailed guidance on designing and developing a 21st century learning in the form of e-learning. Train and design new instructors in the e-learning design orientation and provide basic concepts and information about the processes and resources involved in e-learning. Designing and managing e-learning is a new skill in the 21st century that teachers must have. The method of activities used are training, mentoring, implementation, and evaluation. Participants in the training and mentoring activities were junior high school science teachers from Cirebon, Cirebon, and Indramayu districts. Data in the form of observations and questionnaires were analyzed descriptively. The results of training and mentoring that teachers are able to use e-learning well. Teachers can create a learning space in e-learning that contains student teaching materials. The application of e-learning in each school still has limited facilities and infrastructure. The results of the questionnaire responses showed a positive response to the 21st century training and service activities.